Aquatic Invertebrate Fauna of Matapouri, Northland. - Pohe, Stephen Robert (Auckland University of Technology, 2008)
A study of the aquatic invertebrate communities from two locations (Location 1 and Location 2) within the Matapouri catchment in Northland, New Zealand, was conducted to assess community structure in differing local-scale habitats. Four data collection methods were utilised generating 33,058 adult or larval invertebrates. The sampling methods comprised benthic kick-sampling, sticky trapping, light trapping, and emergence trapping. For the sticky trapping and light trapping, sampling was carried out at three different sites (Sites 1–3) within each location. The sites were situated within three habitat types; native forest, native forest-fringe, and raupo wetland. Emergence trapping also commenced within the three sites, at both locations, but was discontinued after two months, due to the equipment being destroyed by consecutive flooding events (method described in Appendix 1). Benthic sampling was carried out within the Forest and Forest-fringe habitats. Benthic sampling, sticky trapping, and light trapping were carried out following a monthly schedule between June and November 2005. Conductivity, pH, and water temperature measurements were taken concurrently with benthic sampling on a monthly basis, while water velocity and substrate measurements were taken once to assist in habitat characterisation. Overall, 71 taxa were recorded by benthic sampling over the six month period, with a mean of approximately 30 taxa per site per month. In comparison with similar studies elsewhere in New Zealand, a figure of around 30 taxa per sample was high. The benthic macroinvertebrate fauna at all sites was dominated by Trichoptera (19 taxa), Diptera (16 taxa) and Ephemeroptera (10 taxa). This pattern of diversity is similar to that reported in other New Zealand studies. However, in contrast to previous studies, the leptophlebiid mayfly genus Deleatidium was not numerically dominant over the rest of the community, and other leptophlebiid genera (Acanthophlebia, Atalophlebioides, Mauiulus and Zephlebia) were equally represented, possibly reflecting niche partitioning between the groups. The genus Nesameletus was not recorded at any site, despite being one of the core mayfly species in New Zealand streams. The rare mayfly Isothraulus abditus was recorded at one of the forest locations. There are no published records of this species from Northland. Although acknowledged as another of the core New Zealand benthic taxa, the hydropsychid caddisfly Aoteapsyche was not recorded during the study. However, another hydropsychid, Orthopsyche, was commonly recorded, and these may be filling a similar niche to the Aoteapsyche genus. In contrast to the Trichoptera, Diptera, and Ephemeroptera, the Plecoptera fauna was relatively depauperate, probably reflecting the warmer climate of the region and lack of temperature-buffered spring-fed streams. Surprisingly, Zelandobius, a core New Zealand genus, was absent but is regularly recorded in Northland. A species of conservation interest, Spaniocercoides watti, currently recognised as a Northland endemic, was recorded in low numbers. There were no apparent trends in diversity or abundance of benthic invertebrates over time. Also, there were no significant differences in species diversity between the two locations. However, in many cases, taxa were more abundant at Location 2. This may have been due to steeper gradients at Location 2, and the consequent effects on substrate size and streambed stability, as all other physical factors appeared similar between locations. Although several significant differences of individual benthic taxa were recorded, no broad effect of habitat (sites) on species diversity was observable. However, at Location 2, abundances were significantly higher at Site 3 (Forest) compared to Site 2 (Forest-fringe). The reasons were uncertain, but may be attributed to higher retention of allochthonous organic materials, trapped by in-stream cover and larger substrates. Investigations of adult stages by sticky traps supported benthic results recording community compositions and abundances dominated by Trichoptera and Diptera. Plecoptera were poorly represented. Location 2 recorded higher abundances of taxa, particularly Ephemeroptera and Plecoptera. Investigations of adult stages by light traps however did not produce any statistically significant differences in abundances between sites, between locations, or between sites across locations, and it is believed to be due to limited sampling replication combined with some biases of light trapping. This study indicates that the aquatic invertebrate community at Matapouri is diverse but also reasonably representative. Several rare or uncommon insects inhabit the catchment. It is therefore important that Iwi and the local Landcare Group, who invited and supported this research, together with the Department of Conservation, continue their efforts in protecting these areas. The resident fauna have the capacity to restock areas downstream, which are intended to be improved and restored through sediment control and riparian management.
Keywords: Aquatic insects; Community composition; Habitat use; Kick sampling; Benthic macroinvertebrates; Northland; Light trapping; Sticky trapping